Direitos Humanos, financiamento público e ensino superior: orçamento destinado ao Programa Nacional de Assistência Estudantil na Universidade Federal do Tocantins - Araújo Júnior, Carlos Alberto Moreira de (Universidade Federal do Tocantins, 2020)
Promoting human rights has become a consensus since the adoption of the Universal Declaration of Human Rights (UDHR). The broad and inclusive accomplishmentof the human right to education, fundamental to the exercise of other human rights, depends on positive actions by the State through the allocation of resources among the priorities in the public budget. Forthis reason, due to the need to promote it, over the last decades the public budget has been considered as an instrument for the effective implementation of the human right to education, necessary for the financing of inclusive state policies, for example, student assistance after approval the National Student Assistance Program (PNAES). Therefore, this research aimed to analyze the historical trajectory of resource allocation in the period from 2010 to 2018, to mantain the National Student Assistance Program at the Federal University of Tocantins. Sought to understand whether budgetary allocations and public expenditures made with the financing of student assistance, having as a starting point the approval of PNAES, have been successful for the broad and progressive realization of the human right to education in the context Federal University of Tocantins. Due to the nature of its objectives, it is considered an applied research. Due to the collection procedures and technical methodological aspects, this study adopted the bibliographic and documentary research procedures. The critical-dialectic approach guided the analysis of the data that fed this study to meet the objectives and the research problem. Other than this, the data analysis includes both quantitative and qualitative research approaches. The content analysis technique, described by Bardin (2011), was used in view of a better critical understanding beyond the numbers regarding the volume of resources in the execution of the budget destined to the PNAESat Federal University of Tocantins. The data show that in recent years there has been a significant increase in the number of vulnerable students in public higher education in Brazil, highlighting, as a result, the need for the public budget to maintain these students at the university. The results show, on the one hand, that the public budget destined to finance the student assistance policy allows greater democratization of access to higher education, therefore, essential for the realization of the human right to education. On the other hand, in a social reality of contradictions, the current political agenda defends the reduction of the State interference, and attributes to social policies the responsibility for the imbalance in public accounts raising a real challenge to human rights and accentuates the financial crisis of the university. This movement, aligned with the proposal for an operational university, has been gaining more space of action. In summary, the reduction of the budget allocated to the PNAESthreatens the financing of student assistance, signaling an exclusive and instrumental relationship.